Effect of GFRP and steel reinforcement bars on the flexural behavior of RC beams containing recycled aggregate - Rasha A. El-Sadany; Sherif H. Al-Tersawy; Hossam El-Din M. Sallam (Fracture and Structural Integrity)
Concrete containing wastes from the demolition of old deteriorated buildings are produced enormously. Concrete is a brittle matrix that is usually reinforced by ductile reinforcement such as steel bars. However, due to the susceptibility of steel to corrosion, fiber-reinforced polymers (FRP) bars are used as an alternative reinforcement. The main drawback of FRP bars is their brittleness. These two types of reinforcements, i.e., steel and glass FRP (GFRP) bars, have been used in the present work. The flexural behavior of twelve RC beams reinforced with different ratios of GFRP or steel areas containing recycled aggregate has been experimentally studied and compared with beams without recycled aggregate. The present results show that beams reinforced with GFRP and containing recycled aggregate exhibit a lower load-carrying capacity, lower the first crack, and the highest deflection. All GFRP RC beams exhibited brittle failure, i.e., concrete crushing in the compression zone, except one beam, with 2(16 bars and concrete without recycled aggregate, which ruptured GFRP bars. However, ductile failure modes are observed for all beams reinforced with steel bars, i.e., yielding in steel bars followed by concrete failure. The novelty and advantage of the present results are that the large deflection of GFRP RC beams represents enough warning before failure, as found in ductile RC beams